Validation of the Japanese Big Five Scale Short Form in a University Student Sample - Toyomoto, Rie; Sakata, Masatsugu; Yoshida, Kazufumi; Luo, Yan; Nakagami, Yukako; Iwami, Taku; Aoki, Shuntaro; Irie, Tomonari; Sakano, Yuji; Suga, Hidemichi; Sumi, Michihisa; Ichikawa, Hiroshi; et al. (Frontiers in Psychology, 2022)
The Japanese Big Five Scale Short Form (JBFS-SF), a 29-item self-report scale, has recently been used to measure the Big Five personality traits. However, the scale lacks psychometric validation. This study examined the validity and reliability of the JBFS-SF with data collected from 1,626 Japanese university students participating in a randomized controlled clinical trial. Structural validity was tested with exploratory and confirmatory factor analysis and measurement invariance tests were conducted across sex. Internal consistency was evaluated with McDonald’s omega. Additionally, construct validity was estimated across factors using the PHQ-9, GAD-7, AQ-J-10, and SSQ. EFA results showed that the JBFS-SF can be classified according to the expected five-factor structure, while three items had small loadings. Therefore, we dropped these three items and tested the reliability and validity of the 26-item version. CFA results found that a 26-item JBFS-FS has adequate structural validity (GFI = 0.907, AGFI = 0.886, CFI = 0.907, and RMSEA = 0.057). The omega of each factor was 0.74–0.85. Each JBFS-SF factor was specifically correlated with the PHQ-9, GAD-7, and SSQ. This research has shown that the JBFS-SF can be a clinically useful measure for assessing personality characteristics.